(untitled) (Palíndromo, 2021)
This text is a fragment of the ongoing research entitled Conversations about conversations: speaking and listening in contemporary artistic practices. It aims at investigating and proposing ways of thinking and doing pulsate/compulsive writing based on the works that trigger conversation; Planting listening; Numbness Ear / Tired listening and VERSAR podcast from the core of listening and conversations of my artistic production of the last three years, towards a verbal, sonorous, public and participative art, which considers the specificities of vocalization and listening based on experiments and exercises that allow a transition between voice and living writing. To this end, I benefited from artistic theoretical references of contemporary art, street’s song, socio-philosophy and everyday listening.